2016
DOI: 10.1590/s0102-053620160420
|View full text |Cite
|
Sign up to set email alerts
|

Simulação do efeito residual da atrazine em cenoura

Abstract: RESUMO Atrazine é um herbicida recomendado para a cultura do milho, porém há poucas informações sobre seu efeito residual em hortaliças que eventualmente poderão ser cultivadas em sucessão. O objetivo dessa pesquisa foi avaliar a simulação do residual de subdoses de atrazine no substrato sobre o desenvolvimento e produção de cenoura 'Brasília'. Os tratamentos constituíram-se de oito doses decrescentes de atrazine (250, 25,0, 2,5, 0,25, 0,025, 0,0025, 0,00025 e 0 g i.a./ha) partindo da concentração de 1/10 da d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…After eight months of application of atrazine, it was found that the residual effect of the herbicide reduced, on average, 8.3 ton of sugar per hectare. In the study by Furlan et al (2016), the residual effect of atrazine (up to 0.25 kg ha -1 ) has not impacted the percentage of emergency nor the commercial pattern of the carrot.…”
mentioning
confidence: 76%
“…After eight months of application of atrazine, it was found that the residual effect of the herbicide reduced, on average, 8.3 ton of sugar per hectare. In the study by Furlan et al (2016), the residual effect of atrazine (up to 0.25 kg ha -1 ) has not impacted the percentage of emergency nor the commercial pattern of the carrot.…”
mentioning
confidence: 76%
“…Environmental conditions, such as the temperature and type of soil, have a direct influence on the half‐life and biodegradation of atrazine, which may remain in the environment for between 2 and 6 months (Swissa et al, 2015). In the soils of natural environments, Furlan et al (2016) reported a half‐life of between 4 and 385 days, which may increase in deep aquifers. In surface waters, the half‐life lasts 10–105 days in aerobic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, a superfície das argilas pode apresentar valores de pH menores (0,5 a 4,0 unidades) do que o pH da solução do solo, o que possivelmente aumenta a sorção da atrazina por estas frações minerais em condições de pH baixo (VONBERG et al 2014 , sendo que na maior dose aplicada dos herbicidas a redução foi de 95,53% em comparação a testemunha. Fato este que ocorreu em trabalho realizado com a cultura da cenoura, onde a massa seca da parte aérea avaliada aos 29 DAA foi reduzida em 60% para maior dose de atrazina (250 g i.a.ha -1 ) (FURLAN et al 2016). Sendo correspondente as avaliações visuais de fitotoxicidade, onde ambos os herbicidas avaliados não diferiram entre si, o que ocorre devido a quantidade de produto absorvido e translocado aumentar à medida que a dose aumenta.…”
Section: Experimento Em Casa De Vegetaçãounclassified